Commitment and motivation in practicing yoga among adults in Kuching, Sarawak - Cheah, W.L; Chang, Kam Hock; Muhammad Affan, Azmi; Najihah Ayuni, Md Hamsani; Yek, En Ci; Yeap, Yi Ni (NISCAIR-CSIR, India, 2017)
This study aims to identify the motivational factors that influence yogis and their commitment in yoga in Kuching. A cross-sectional study was conducted using the Self-Motivation Scale (SMS 28) and Sport Commitment questionnaires. A total of 109 respondents participated with a mean age of 40.1 years (SD = 10.16), mean Body Mass Index (BMI) of 23.1 kg/m2 (SD = 3.98). There were more female respondents, accounting for 86.2 % of total participation. More than 40 % of the participants were Hatha yoga practitioners. Those who were above 40 years of age were found to have higher intrinsic motivation (mean = 4.3, SD = 0.55) and extrinsic motivation (mean = 3.9, SD = 0.65) as compared to the younger age group (p < 0.05). Similarly, those who practiced yoga for more than 5 yrs were found to have higher extrinsic motivation (mean = 4.0, SD = 0.78) compared to those who practiced for a shorter duration (p < 0.05). This survey found that intrinsic motivation remains the highest motivation in practicing yoga, indicating its potential role in helping yoga practitioners in sustaining their practices. Both intrinsic motivation and extrinsic motivation were found to be associated with sport commitment. More promotion on the goodness of yoga should be carried out to encourage all segments of society regardless of age, gender and races into practicing yoga.